Propagação clonal de genótipos superiores de erva-mate cv. Cambona 4 em diferentes substratos - Fonseca, Debora Aline da (2017)
The Cambona 4 yerba mate, the first bi-parental progeny selected in Brazil, has been planted by the softer flavor and high productivity. However, although the plants exhibit greater uniformity, variations in the phenotypic, productive and chemical characteristics of the leaves occur due to the seed origin of the seedlings. The use of cuttings can be a viable alternative for the multiplication of genetically superior genotypes. The objective of this research was to evaluate the rooting potential of superior genotypes of 'Cambona 4' in different combinations of carbonized rice husk (CAC) and commercial substrate based on pine bark and coconut fiber (SC). Eight genotypes were evaluated in five mixtures of substrates (100%CAC, 75%CAC/25%SC, 50%CAC/50%SC, 25%CAC/75%SC and 100%SC. The cutting was done at the end of January (summer), in an agricultural greenhouse with intermittent misting, using 12 cm apical semilenous cuttings, maintaining two half leaves. The cutting was done in tubes (140 cm3), treating the stakes with 6000 mg L-1 of IBA. The results allowed to conclude that 'Cambona 4' grasses present superior genotypes in productivity with high rooting potential by cuttings. The genotypes CB6 and CB7 stood out for the best rooting, superior to75%. There was a correlation between leaf retention and rooting percentage. The commercial substrate combinations with carbonized rice husk resulted in denser mixtures, with lower porosity, greater supply of available water and nutrients, providing satisfactory rooting and, possibly, conditions for the continuity of the growth of the seedlings without the need of being transplanted to another substrate.